Legal Position of Advocates as Law Enforcers Equal to Judges and Prosecutors in the Indonesian Criminal Justice System - Riyandra, Reza; Sara, Rineke (Jurnal Greenation Sosial dan Politik, 2025)
This study aims to analyze the legal position of advocates as law enforcers who are equal to judges and prosecutors in the criminal justice system in Indonesia. Advocates have an important role in the judicial process as defenders of the defendant's rights and in maintaining justice at every trial stage. This study examines in depth the role of advocates based on existing regulations, especially Law Number 18 of 2003 concerning Advocates, and its implications in criminal justice practices. Although advocates are recognized as part of the justice system, in practice, there are still challenges related to their equality and independence in the legal process. The results of this study indicate that although constitutionally recognized, strengthening the position of advocates in the Indonesian criminal justice system still requires more attention, especially about the relationship between advocates, judges, and prosecutors to achieve balanced and impartial justice.